NOAA Weather Satellite Station at KUTKM - Hwa, Ho Yih; Manap, Zahariah; Haroon, Hazura (2006)
A ground station has been installed at Kolej Universiti Teknikal Kebangsaan Malaysia (KUTKM) to receive the VHF signal form the United State National Oceanographic and Atmospheric Administration (NOAA) Low Earth Orbiting Satellite (LEO) weather satellite series. The satellite signal was received and decoded as image which was displayed on computer screen in the form of visible light, infra-red or the combination of both. The image file is then processed and stored into a local computer for meteorology study in KUTKM.